2017
DOI: 10.29244/jpsl.7.1.41-50
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tipologi Tutupan Vegetasi Sebagai Dasar Penyusunan Strategi Restorasi Di Area Iuphhk-Re Pt Reki

Abstract: Harapan rainforest situated in South Sumatera is a restoration area of PT REKI company that highly susceptible to land conversion. The problem faced in the effort of restoration is the restorated area that is too large and has not been tested any silvicultural techniques. The condition of land cover is the basic information that could be used as a reference in the preparation of restoration strategy. The study aimed to determine the level of damage, the condition of the ecosystem, appropriate silvicultural tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…The study resulted in a negative exponential equation of stand structure of trees with dbh ≥ 20 cm before gap opening and planting The stand density of various diameter size before and after gap opening and planting showed a decrease in the number of individuals along with the increase in diameter size. The same pattern was observed in many studies in Indonesia such as reported by Indrawan (2000), Nurfatma et al (2017), andPamoengkas et al (2019), in Malaysia reported by Siti Nurfaeiza et al ( 2022), Ahmad Rohaiza et al (2022), and in Ethiopia reported by Gebeyehu et al (2019).…”
Section: Resultssupporting
confidence: 85%
“…The study resulted in a negative exponential equation of stand structure of trees with dbh ≥ 20 cm before gap opening and planting The stand density of various diameter size before and after gap opening and planting showed a decrease in the number of individuals along with the increase in diameter size. The same pattern was observed in many studies in Indonesia such as reported by Indrawan (2000), Nurfatma et al (2017), andPamoengkas et al (2019), in Malaysia reported by Siti Nurfaeiza et al ( 2022), Ahmad Rohaiza et al (2022), and in Ethiopia reported by Gebeyehu et al (2019).…”
Section: Resultssupporting
confidence: 85%
“…There are differences in the number of species in each region due to variations in environmental conditions. Different environmental characteristics will create different compositions of vegetation [15]. The seedlings and understorey have the greatest number which are 1028 in total, while trees had the lowest, with only 72 individuals (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Perhitungan sumberdaya alam (anakan pohon) dilakukan dengan mempertimbangkan harga bibit tanaman hutan di pasar dikurangi dengan biaya produksinya. Hopea mengarawan menjadi salah satu spesies kunci yang direkomendasikan untuk kegiatan pengkayaan tanaman karena jenis ini memiliki kelebihan cepat tumbuh dan lebih tahan naungan (Nurfatma, et al 2017) Hasil menunjukkan bahwa anakan tingkat pancang jenis hopea menyebar secara mengelompok sebagaimana ditunjukkan pada Tabel 4. Sedangkan untuk jenis shorea tidak dapat didefinisikan karena masing-masing jenis hanya ditemukan 1 individu dari 18 plot pengamatan.…”
Section: Analisis Dataunclassified